Role of the Protective Factors in The Resilience of The Migrant Workers in Tamil Nadu - Singh, Aruna; Vijila, Dr. Y. (Migration Letters, 2024)
This research explores the complex influence of various protective elements on the resilience levels among Tamil Nadu’s migrant labour force, focusing on the ways through which social, economic, psychological, and legislative factors bolster their capacity to endure, adapt to, and rebound from migration-induced hardships Data collection was carried out using a structured survey distributed to 411 migrant labourers in the Tiruchirappalli district of Tamil Nadu. This survey included questions about demographic details and various dimensions of protective factors like mobility, Informal entrepreneurship, structural adaptation, language acquisition, labour market, and optimism, rated on a seven-point Likert scale. Through Structural Equation Modelling (SEM) and Confirmatory Factor Analysis (CFA), the analysis revealed that the most significant predictors of protective factors on the well-being of migrant workers were the ease of structural adjustment(structural adaptation) and the potential for engaging in informal entrepreneurship(Informal entrepreneurship), supplemented by language proficiency(Language Acquisition), mobility access(mobility), and the ability to compete in the job market (labour market) By providing new insights into the specific conditions of Tamil Nadu’s migrant workers, the research informs policy-making and practical interventions aimed at enhancing their quality of life and work, promoting effective integration, and ensuring their overall mental and physical well-being in the face of migration challenges. The findings advocate for a comprehensive strategy towards migrant welfare, highlighting the essential role of governmental bodies, NGOs, and community initiatives in creating a supportive framework for this demographic.